"Dear Alex" an online interactive digital comic about autism - Arceo, Klaudine Paola C.
Autism is a social disorder that was first identified by Leo Kanner. Autism is a growing disorder in the world today and even though there is more information about the disorder, researchers are still unable to truly uncover what causes autism. For people diagnosed with autism, they have trouble in socializing with others, and the severity of their autism determines how they interact with others. In the diagnosis of a person with autism, there is a behavioral checklist that doctors look out for. According to the World Health Organization (WHO), autism becomes evident on children from ages 5 or below. There are number of social behaviors that can be identified as autism and the American Psychiatric Association has determined that autism is a spectrum and a number of traits can be seen in the Autism Spectrum Disorder (ASD) umbrella such as asperger syndrome.